(untitled) (Agricultural Engineering, 2016)
The paper presents the analysis of use of IT technologies by farmers. Data from a research survey carried out in 100 randomly selected farms in 2015 constituted research material. The research area covered farms located in Podlaskie Voivodeship on the area of two counties i.e. Wysokie Mazowieckie (50 questionnaires) and Zambrów County (50 questionnaires). The questionnaire is a research instrument. The research was to determine the level of use of specialist computer programs by farmers and their needs concerning acqui sition of information on innovations in agriculture. Due to the obtained results one may find out that a low number of farmers uses specialist computer programs in their farms. In Wysokie Mazowieckie County it is only 8% of respondents and in Zambrów County 14%. The main source of infonnation on innovations in agriculture is the Internet, professional agricultural press and television.